KEY ASPECTS OF MANAGING THE INNOVATION CLIMATE OF THE ORGANIZATION - Mitrushova Marina Leonidovna (Journals Park Publishing, 2025)
The article presents an overview of theoretical research devoted to the innovative climate of the organization. The emphasis is placed on the importance of the level of environmental favorability when assessing the innovative climate of the organization. The content of managing the innovative climate of the organization is revealed, which is determined by the composition of the methods and functions carried out during the preparation and implementation of events related to the creation of innovations and their embodiment in innovations. Aspects of managing the innovative climate of the organization are analyzed.
Keywords: Innovation climate; organization; industrial production; management; innovation; novelty; innovation potential; organizational environment.